Long‐term morbidity of respiratory viral infections during chemotherapy in children with leukaemia. Issue 11 (8th August 2019) - Lin, Beryl; Kennedy, Brendan; McBride, Jamie; Dalla‐Pozza, Luciano; Trahair, Toby; McCowage, Geoffrey; Coward, Emma; Plush, Leanne; Robinson, Paul D.; Hardaker, Kate; Widger, John; Ng, Anthea; et al.
Abstract: Background: Respiratory viruses are a common cause of infection in immunosuppressed children undergoing cancer therapy. Pulmonary sequelae have been documented following respiratory viral infections (RVIs) in hematopoietic stem cell transplant (HSCT) recipients; however potential late effects in children undergoing nonmyeloablative chemotherapy have not been investigated. Aim: To evaluate the long‐term pulmonary morbidity of respiratory viral infections during chemotherapy in children with acute lymphoblastic leukemia (ALL). Methods: Childhood ALL survivors, aged 7 to 18 years, greater than 6 months posttreatment were recruited. Exclusion criteria included HSCT or proven bacterial/fungal respiratory infection during treatment. Subjects were classified into "viral" or "control" groups according to retrospective medical records that documented the presence of laboratory‐proven RVIs during chemotherapy. Symptom questionnaires (Liverpool, ISAAC) and lung function testing (spirometry, plethysmography, diffusing capacity, forced oscillation technique to ATS/ERS standards) were then performed cross‐sectionally at the time of recruitment. Results: Fifty‐four patients (31 viral, 23 control) were recruited: median (range) age 11.2 (7.2‐18.1) years, and at 4.9 (0.5‐13) years posttherapy. Abnormalities were detected in 17 (31%) individuals (8 viral, 9 control), with the most common being DLCO impairment (3 viral, 4 control) and reduced respiratory reactance at 5 Hz (5 viral, 6 control). Children with RVIs during chemotherapy reported more current respiratory symptoms, particularly wheeze (odds ratio [OR], 3.0; 95% confidence interval [CI]: 0.9‐10.0; P = .09) and cough (OR, 2.7; 95% CI: 0.8‐9.5; P = .11). No differences in lung function tests were observed between the two groups. Conclusions: Our study found children with RVIs during chemotherapy developed more long‐term respiratory symptoms than controls; however, differences did not reach statistical significance. No differences in static lung function were found between the two groups. Overall, pulmonary abnormalities and/or significant ongoing respiratory symptoms were detected in nearly a third of ALL survivors treated without HSCT. Larger, prospective studies are warranted to evaluate the etiology and clinical significance of these findings.